NORMALITY VS. ABNORMALITY IN A CHILD’S BEHAVIOR (A SEMIOTIC PERSPECTIVE) - Hoxha, Bujar (European Scientific Journal, ESJ, 2014)
Taking a child’s behavior as an example (out of my own experience), I shall try to consider a theoretical framework on which a semiotic model can be established. This can, in my opinion, be performed owing to the fact that semiotics initially establishes a relation between two (or more than two) phenomena, which can then be subordinated to a process of signification. My aim in this paper shall be to establish a theoretical limit to such oppositional relations in terms of a child’s behavior (such as: normality vs. abnormality, intentionality vs. unintentionality, etc.), which may emerge from various states of a mental disorders such as Autism presents. Such states can gain their transformability through procedures such as: transformation in semiotics, and new behavior acquisition in psychology, so as to become moveable from one state to another. The questions I am trying to answer are: are such phenomena treatable in terms of their becoming passionate? If an abnormal behavior comes into existence, how is it expressed through the incapacity of the “symbolic representation,” as Piaget claims? And finally, which is the way to understand such a child’s’ requests and complaints?